Continuous real time 3D motion reproduction using dynamic MRI and precomputed 4DCT deformation fields. Issue 8 (2nd July 2020) - Dasnoy‐Sumell, Damien; Souris, Kevin; Van Ooteghem, G.; Macq, Benoit
Abstract: Radiotherapy of mobile tumors requires specific imaging tools and models to reduce the impact of motion on the treatment. Online continuous nonionizing imaging has become possible with the recent development of magnetic resonance imaging devices combined with linear accelerators. This opens the way to new guided treatment methods based on the real‐time tracking of anatomical motion. In such devices, 2D fast MR‐images are well‐suited to capture and predict the real‐time motion of the tumor. To be used effectively in an adaptive radiotherapy, these MR images have to be combined with X‐ray images such as CT, which are necessary to compute the irradiation dose deposition. We therefore developed a method combining both image modalities to track the motion on MR images and reproduce the tracked motion on a sequence of 3DCT images in real‐time. It uses manually placed navigators to track organ interfaces in the image, making it possible to select anatomical object borders that are visible on both MRI and CT modalities and giving the operator precise control of the motion tracking quality. Precomputed deformation fields extracted from the 4DCT acquired in the planning phase are then used to deform existing 3DCT images to match the tracked object position, creating a new set of 3DCT images encompassing irregularities in the breathing pattern for the complete duration of the MRI acquisition. The final continuous reconstructed 4DCT image sequence reproduces the motion captured by the MRI sequence with high precision (difference below 2 mm).